Description Of C-Reactive Protein (CRP) In Patients With Type 2 Diabetes Mellitus At Mulyorejo Health Center In Malang City - Kapero, Febriyanti Wora; Mahtuti, Erni Yohani; Rahmawati, Previta Zeizar (Poltekkes Kemenkes Mataram, 2023)
Diabetes Mellitus Type 2 is a metabolic disorder condition characterized by hyperglycemia, due to decreased insulin secretion. Many cytokines play a role in the acute phase response, so that markers such as CRP increase in patients with type 2 DM. The type of research used in this study is descriptive research, which describes the results of CRP examination in patients with type 2 diabetes. Examination of respondents' serum C-Reactive Protein (CRP) levels was carried out qualitatively using the Latex Agglutination method and followed by a semi-quantitative method, namely dilution to determine the level of inflammation. The results of CRP examination on 30 serum samples that have been carried out on patients with Type 2 Diabetes Mellitus found that 29 (96.7%) were positive and 1 (3.3%) of respondents were negative. The group of CRP levels for titer 12 was 5 samples (16.7%), titer 24 was 17 samples (56.7%), titer 48 was 5 samples (16.7%), and titer 96 was 2 samples (6.7). %). The results of the four groups with the highest CRP levels, namely a titer of 24 mg/L as many as 17 samples (56.7%) showed that some of the CRP levels were higher than normal. Conclusion Almost all respondents with type 2 Diabetes Mellitus had positive C-Reactive Protein examination results and a small proportion of type 2 Diabetes Mellitus patients had negative C-Reactive Protein examination results.